Particle Flow Analysis of Acoustic Emission Features of Rock under Rock Burst Stress Path - Yalei Wang; Jinming Xu (Geofluids)
The AE (acoustic emission) features could reflect the process of fracture initiation and propagation in rocks. Taking Lalin railway tunnel granite as an example, a three-dimensional particle flow numerical model of rock was established based on the PFC (particle flow code). The mechanical properties between particles were simulated using parallel bond. The rock burst stress path was simulated using the movement of the wall in the particle flow model. The results of uniaxial compression tests in a laboratory were used to calibrate the mesoscale mechanical parameters of the particle flow model. AE features of rock deformation and failure under different confining pressures were then studied. It shows that the unloading direction of rock may produce strong dilatation deformation during rock burst; with the increase of confining pressure, the more obvious dilatation deformation and the more possibility of serious rock burst to occur; the unloading failure of rock reveals that rock burst is a mixed failure of tensile and shear, and the tensile cracks account for about 70%; the number of AE events of rock unloading failure occur at the top and bottom of the rock first and then expand rapidly to the middle part until the rock is completely destroyed; in the process of rock burst, AE rupture strength is relatively concentrated, the number of AE events surge obviously, and the number of AE events in surge period account for more than 80% of all AE events. The results presented herein may be referable in analyzing the mechanism of rock burst.